The effect of titanium surface treatment by application of constant potential or current on the viability of pre-osteoblast cells: an in-vitro study - Cai, Wenji; Wang, Min; Hadad, Amir Ei; Zhang, Yuli; Tran, Simon D.; Shurbaji, Samar; Nasrallah, Gheyath K.; Sanz, Mariano; Omanovic, Sasha; Tamimi, Faleh (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives The aim of this study was to investigate the impact of electrochemical treatment of a titanium surface employing constant current and potential on the viability of the tissue cells attached to the surface and determining the safety limits for this type of treatment. Methods Pre-osteoblast cells (pOB) were cultured and seeded onto titanium discs. The cell-seeded discs were then exposed to a range of contant direct electrical potentials (-6V–6V) or contant direct electrical currents (−12.5 mA, −25 mA, or −50 mA) using a three-electrode system connected to a potentiostat. Cell viability was assessed using live/dead assay and fluorescence microscopy. Results Exposure of cells to high negative potentials caused cell detachment, while exposure to positive ones led to cell death on the cpTi surfaces. However, cellular viability was preserved when the electrical potentials were kept between −3 and +3 V. Cells retained 80% viability when subjected to −12.5 mA currents with an initial pOB cell count of 5 × 104. However, when the initial cell count was elevated to 1 × 105, the cells demonstrated the ability to withstand an even greater current (−25 mA) while preserving their vitality at the same level. Conclusion Treatment of a titanium dental implant surface employing constant potential or current can harm cells surrounding dental implants. However, this damage can be minimized by keeping the potential within a safety limit.